Analysis of Mason-Pfizer Monkey Virus Gag Domains Required for Capsid Assembly in Bacteria: Role of the N-Terminal Proline Residue of CA in Directing Particle Shape - Rumlova-Klikova, Michaela (American Society for Microbiology, 2000)
Mason-Pfizer monkey virus (M-PMV) preassembles immature capsids in the cytoplasm prior to transporting them to the plasma membrane. Expression of the M-PMV Gag precursor in bacteria results in the assembly of capsids indistinguishable from those assembled in mammalian cells. We have used this system to investigate the structural requirements for the assembly of Gag precursors into procapsids. A series of C- and N-terminal deletion mutants progressively lacking each of the mature Gag domains (matrix protein [MA]-pp24/16-p12-capsid protein [CA]-nucleocapsid protein [NC]-p4) were constructed and expressed in bacteria. The results demonstrate that both the CA and the NC domains are necessary for the assembly of macromolecular arrays (sheets) but that amino acid residues at the N terminus of CA define the assembly of spherical capsids. The role of these N-terminal domains is not based on a specific amino acid sequence, since both MA-CA-NC and p12-CA-NC polyproteins efficiently assemble into capsids. Residues N terminal of CA appear to prevent a conformational change in which the N-terminal proline plays a key role, since the expression of a CA-NC protein lacking this proline results in the assembly of spherical capsids in place of the sheets assembled by the CA-NC protein.